أوقات العمل بالدوريات و تأثيره على حوادث العمل - ناتش, فريد (جامعة الوادي - University of Eloued, 2022)
تهدف الدراسة الحالية إلى الكشف عن أثر نمط أوقات العمل بالدوريات على معدل حوادث العمل لدى عمال المؤسسة الوطنية للنظافة بالجزائر العاصمة. وتكونت عینة الدراسة من (150)عامل لسنة (2020)، والذین تم اختیارهم بطریقة قصدية حسب المنهج الوصفي واستخدم الباحث استبیان من إعداده حول نمط أوقات العمل بالدوريات وحوادث العمل، وبعد المعالجة الإحصائیة توصلت نتائج الدراسة إلى عدم وجود فروق في درجة حوادث العمل حسب ساعات العمل في الدوريتين الصباحية والليلية لدى عمال المؤسسة. Abstract: The objective of this study is to identify the impact of the work-study model on occupational accidents of operators within the national cleanling company (net com) in the city of Algiers. The study sample consisted of (150) workers for the year (2020),who were intentionally chosen using the descriptive approach. The researcher used a questionnaire prepared according to working time, shift and work accidents, after statistical processing the results of the study revealed that there no differences in the degree of accidents at work according to the hours of work and the day shift and the night shift.
مقال
Keywords: أوقات العمل ; العمل ; الدوريات ; حوادث العمل; work time; work; periodicals; work accidents